Aisha siddique - Khan, Saniyasnain (Goodword Books Place of publication not identified, 2012)
"Aisha Siddique" by Khan Saneysea explores the life and contributions of Aisha bint Abi Bakr, a prominent figure in Islamic history known for her intelligence, scholarship, and role in early Muslim society.